DEVELOPMENT OF A NEW STUDENT ADMISSION SERVICE INFORMATION SYSTEM - Muhammad Reza Redo; Sulistiyanto Sulistiyanto (PT. Alesha Media Digital, 2022)
Dharma Wacana is the first tertiary institution in computer science in the Metro Indonesia area. The registration system is done by coming directly to the campus and has not used the website media. In development, research is carried out using the Waterfall model by building a system. Besides that, data collection is carried out using the method of observation and literature study. The implementation of the Waterfall model is explained using mapping diagrams, context diagrams, DFD, database table structures, relations between tables, and input-output design. This website-based information system aims to improve services to the public in the form of information and new student registration that can access online. And it is hoped that it will enhance Campus management to take advantage of this online registration data as a basis for Promotion.